Comparing Supervised Learning Techniques on the Task of Physical Activity Recognition - Dalton, A.; OLaighin, Gearóid (IEEE journal of biomedical and health informatics, 2013)
The objective of this study was to compare the performance of base-level and meta-level classifiers on the task of physical activity recognition. Five wireless kinematic sensors were attached to each subject ( n = 25) while they completed a range of basic physical activities in a controlled laboratory setting. Subjects were then asked to carry out similar self-annotated physical activities in a random order and in an unsupervised environment. A combination of time-domain and frequency-domain features was extracted from the sensor data including the first four central moments, zero-crossing rate, average magnitude, sensor cross correlation, sensor autocorrelation, spectral entropy, and dominant frequency components. A reduced feature set was generated using a wrapper subset evaluation technique with a linear forward search and this feature set was employed for classifier comparison. The meta-level classifier AdaBoostM1 with C4.5 Graft as its base-level classifier achieved an overall accuracy of 95%. Equal sized datasets of subject-independent data and subject-dependent data were used to train this classifier and high recognition rates could be achieved without the need for user specific training. Furthermore, it was found that an accuracy of 88% could be achieved using data from the ankle and wrist sensors only.